2007
DOI: 10.1002/app.26984
|View full text |Cite
|
Sign up to set email alerts
|

Chemical resistance, void contents, and morphological properties of Hildegardia fabric/polycarbonate‐toughened epoxy composites

Abstract: A uniaxial natural fabric of Hildegardia populifolia was used as a reinforcement for a polycarbonatetoughened epoxy. The Hildegardia fabric was treated with a 5% sodium hydroxide solution for 1 h. The fabric was spray-coated with a 1% silane-based coupling agent. The variation of the chemical resistance and void content with different fabric contents and fiber orientations was studied. The morphology of the fractured composites was investigated with scanning electron microscopy (SEM). SEM micrographs indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Generally, the percentage absorption was larger for aqueous solutions, and this was to be expected as a result of the hydrophilicity of the fiber. This conclusion is supported by the weight increase in the presence of these liquids with increasing fiber content . Figure shows the percentage absorption of bamboo epoxy composites for different samples.…”
Section: Resultsmentioning
confidence: 61%
“…Generally, the percentage absorption was larger for aqueous solutions, and this was to be expected as a result of the hydrophilicity of the fiber. This conclusion is supported by the weight increase in the presence of these liquids with increasing fiber content . Figure shows the percentage absorption of bamboo epoxy composites for different samples.…”
Section: Resultsmentioning
confidence: 61%
“…Chen et al observed a remarkable hike in the mechanical properties of epoxy by the incorporation of epoxidized soybean oil. Guduri et al used natural fabric of Hildegardia populifolia to reinforce polycarbonate toughened epoxy. They observed both enhanced chemical and water resistance in epoxy composites when compared with the neat epoxy.…”
Section: Other Toughening Agentsmentioning
confidence: 99%
“…Rajulu outlines the chemical properties of natural fibers composites and discusses the latest trends in chemical modification mechanisms [15]. Guduri used uniaxial natural fabric of Hildegardia populifolia as reinforcement for a polycarbonate toughened found to have reasonable chemical and water resistance [16]. Jayaramudu used Polyalthiacerasoide woven fabrics as reinforcements of epoxy and these hybrid composites showed resistance to acids, alkalis and various solvents and also possessed lower water absorption [17].…”
Section: Introductionmentioning
confidence: 99%